Mubadalah in Divorce Rights: Interpretation of QS. An-Nisa Verse 128-130 Perspective of Gender Justice Reason - Matsna Khuzaimah; Shinta Nurani (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
This article discusses gender justice in divorce rights in QS. an-Nisa verses 128 - 130 from the perspective of understanding mub is Faqihuddin Abdul Kodir. The purpose of this study was to determine the interpretation of QS. Al-Nisa verses 128 -130 according to Faqihuddin Abdul Kodir and the concept of divorce rights in the frame of gender justice perspective mafhum mub is Faqihuddin Abdul Kodir. The method used in this research is qualitative using the approach of Jorge G Gracia's Hermeneutic Theory of Interpretation. The results of this study indicate that the interpretation of the right to divorce in QS. an-Nisa verses 128 -130 according to Faqihuddin Abdul Kodir are about the husband's turning away from his wife (Surat al-Nisa: 128), polygamy (Surat al-Nisa: 129), and the way to ask for a divorce (Surat al-Nisa: 130). Therefore understanding mub is to use the interpretation of the QS. Al-Nisa verse 128 - 130, Faqihuddin Abdul Kodir in accordance with the principles of gender justice, namely placing women and men in their rights, without hurting himself, the children and also the family around him